Способ прогнозирования износостойкости твердосплавных режущих инструментов - Нестеренко В. П. Владимир Петрович; Клопотов В. Д. Владимир Дмитриевич; Пилипенко В. А. Владимир Александрович; Заверткин С. Д. Сергей Дмитриевич; Кирсанов С. В. Сергей Васильевич; Арефьев К. П. Константин Петрович
опубл. 20.03.06